Post-processed climate dataset for the Sierra Nevada de Santa Marta (SNSM) Region in Colombia - Valencia Gómez, Jefferson; Frankenberger,Jane; Cherkauer, Keith; Martin López, Javier Mauricio; Monserrate Rojas, Fredy Alexander; Silva, Mayesse Aparecida da (2022)
Monthly cleaned gap-filled climate dataset, derived from raw daily data from the Institute of Hydrology, Meteorology and Environmental Studies (IDEAM by its Spanish name), for a 30-year climate period, from January 1, 1989, to December 31, 2018. This dataset contains monthly precipitation (prec) and monthly maximum (tmax) and minimum (tmin) temperature as tabular time series (CSV) as well as spatial surfaces (GeoTIFF) interpolated at 1 km of spatial resolution. In addition, 1-km spatial surfaces of potential evapotranspiration (pet) are also provided. METHODOLOGY: IDEAM stations within a buffer distance of 15 km of the study area were selected, resulting in 10 stations with daily precipitation data and 5 with daily maximum and minimum temperature data that were subject to quality control. Data were cleaned to remove values out of range, statistical outliers, repetitive measurements during five days, and measurements that changed excessively between two consecutive days following the procedures of Esquivel et al. (2018). Gaps in the daily weather data were filled using the nearest neighbor algorithm bounded by elevation (de Lima et al., in review). The gap-filled data was aggregated to a monthly time-step and consecutively monthly surfaces were generated for each year through spatial interpolations at 1 km of resolution (approx. 30 arc-seconds) by using the thin-plate spline smoothing method from ANUSPLIN version 4.4, which in turn, uses elevation as a covariate (Hutchinson and de Hoog, 1985). Five additional synthetic stations per variable were created for the interpolation based on the weather stations. Finally, monthly surfaces at 1 km of spatial resolution were generated using the modified equation of Hargreaves stated by Droogers & Allen (2002).